2009
DOI: 10.4103/0970-0218.58389
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of bronchial asthma in Indian children

Abstract: Background:The prevalence of childhood bronchial asthma and allergic disease has increased in developed countries. Studies have identified asthma among Indian children. Still, there is paucity of information on the overall prevalence of childhood asthma in India.Objective:To assess time trends and the overall prevalence rate of bronchial asthma among Indian children.Materials and Methods:Literature search for data sources was done through an extensive search in indexed literatures and website-based population … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
83
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(102 citation statements)
references
References 27 publications
10
83
0
Order By: Relevance
“…Rise in prevalence of childhood asthma is a matter of concern worldwide and in India also. [2][3][4][5] The steady rise in prevalence is correlated with demographic changes in city like increase in number of industries, increased density of population from migration of rural population and increased number of automobiles to commute resulting in air pollution. 5 Data on prevalence of asthma is now available from several countries.…”
Section: Introductionmentioning
confidence: 99%
“…Rise in prevalence of childhood asthma is a matter of concern worldwide and in India also. [2][3][4][5] The steady rise in prevalence is correlated with demographic changes in city like increase in number of industries, increased density of population from migration of rural population and increased number of automobiles to commute resulting in air pollution. 5 Data on prevalence of asthma is now available from several countries.…”
Section: Introductionmentioning
confidence: 99%
“…The signs and sympto ms of Asthma depend on bronchospasm, inflammation & narrowing of airway, hyper sensitivity of bronchiols and disturbances in bronchodilators and corticosteroids 1 . In India, the prevalence of asthma is found to be about 2.4% in adults over 15 years of age using the International Union agains t Tuberculosis and Lung Disease (IUATLD) questionnaire 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Thus PFGE proved to be a useful tool for surveillance of the disease in an area. In a previous study based on PFGE indicated the evolutionary aspects where the type 7 and type 1 isolates of S. dysenteriae were probably evolved from a same precursor, while the type 2 and S. flexneri type 2a were probably evolved and diversified from a common progenitor (Pal et al, 2013). PFGE analysis of certain strains of Shigella isolates in Bangladesh showed that S. sonnei biotype a strain was genetically more diverse than biotype strains of other Shigell isolates, and revealed that strains having different integron patterns belonged to different clusters Ud-Din et al, 2013).…”
Section: Shigella Sppmentioning
confidence: 99%